2016
DOI: 10.4103/0972-2327.167706
|View full text |Cite
|
Sign up to set email alerts
|

Ventilators in ICU: A boon or burden

Abstract: Background and Aims:Ventilator-associated pneumonia (VAP) is a major challenge in intensive care units (ICUs). This challenge is even more discernible in a neurological setting owing to the predispositions of patients. Data on VAP in the neurology and neurosurgery ICUs (NNICUs) are scanty in developing countries. This study was conducted to find out the occurrence of VAP, its risk factors, microbiological profile, and antibiotic resistance in patients admitted to the NNICU of a tertiary care institute in India… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…Higher incidence of VAP has been reported in patients with neurocritical illness [15]. In our study, 18.9% (20/106) of the VAP cases were initially admitted to ICU due to neurological disease.…”
Section: Discussionmentioning
confidence: 53%
“…Higher incidence of VAP has been reported in patients with neurocritical illness [15]. In our study, 18.9% (20/106) of the VAP cases were initially admitted to ICU due to neurological disease.…”
Section: Discussionmentioning
confidence: 53%
“…14 15 In a study from North India, Mehndiratta, et al have reported isolates of Pseudomonas, Klebsiella and E. coli with 100% sensitivity to imipenem and all the gram-positive isolates studied were sensitive to linezolid. 16 In this study,the most effective antibiotic against gram negative bacilli was found to be Imipenem followed by Piperacillin tazobactam. An Indian study by Patil have reported Piperacillin Tazobactam, amikacin, and meropenem as good antibiotic options for VAP to start with till culture reports are available.…”
Section: Discussionmentioning
confidence: 70%
“…[23] Increased VAP incidence has been observed in patients with neurological disorders. [24] In our study, 14.46% (23/159) of the VAP patients were admitted due to neurological disease and 30-day mortality in these patients was 47.8% (11/23). Our study shows that the incidence of VAP decreased over the years due to awareness and better management strategies.…”
Section: Discussionmentioning
confidence: 99%